Prices, Profits, and Preference Dependence1. (December 2015) - Chen, Yongmin; Riordan, Michael H.
Abstract : We develop a new approach to discrete choice demand for differentiated products, using copulas to separate the marginal distribution of consumer values for product varieties from their dependence relationship, and apply it to the issue of how preference dependence affects market outcomes in symmetric multiproduct industries. We show that greater dependence lowers prices and profits under certain conditions, suggesting that preference dependence is a distinct indicator of product differentiation. We also find new sufficient conditions for the symmetric multiproduct monopoly and the symmetric single‐product oligopoly prices to be above or below the single‐product monopoly price.